PENGGUNAAN INSTAGRAM SEBAGAI MEDIA PEMBELAJARAN DALAM MENINGKATKAN PRESTASI BELAJAR BAHASA ARAB MAHARAH KALAM MTs SABILUL MUTTAQIN MOJOKERTO - Fitriyah, Khoirunnisa'il (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2020)
Arabic is a unique subject because it has many features and also has many problems. Arabic language is also a subject that must be implemented in every madrasa, starting from madrasah ibtidaiyah, tsanawiyah, aliyah and even universities. Because even though Arabic is not part of the official language of the State of Indonesia but Arabic is part of the Islamic religion. Teaching Arabic is not easy, the biggest problem that must be known by the speakers of Arabic subjects is the motivation to learn Arabic for students. One effort that can be done by a teacher in increasing students' motivation to learn Arabic is through developing the use of instructional media. This study aims to determine the use of Instagram as a medium of learning in improving the learning achievement of Arabic Maharah Kalam / MTS Sabilul Muttaqin Mojokerto speaking skills. In this study using descriptive qualitative research methods and data collection techniques using observation, interviews and documentation. The data sources are Mts Sabilul Muttaqin class XB students, and Arabic subject teachers. The results of this study stated that Instagram media can improve students' Arabic learning achievement, especially in the Maharah Kalam.